Currículo e seus significados para os sujeitos de uma escola ribeirinha, multisseriada no município de Cametá - Pará - PINHEIRO, Maria do Socorro Dias (2009)
The present research investigates the Curriculum and its meanings for the citizens of a riparian, multisseries school in the city of Cametá-Pará, in which if it objectified to analyze how is defined and materialized the curriculum in the multisseries riparian school, identifying which meanings are attributed to the pertaining school curriculum for the pupils, parents, communitarian and the teacher. This study was developed in the Joroca Island, in the locality Jorocazinho de Baixo, a community with a good organizational base, that has been interesting for scientist in other areas; it was benefited with some projects of the federal government and possessed four schools around it. The inquiry occurred in the Elementary Municipal School Jorocazinho, where was searched to initially know the context of the riparian community in the field of the educative practical organizations and its observing which curriculum experiences they have been living and, after that was prioritized to understand the materialization of the curriculum and its meanings in the voice of the citizens of the school. In this direction, the learners, parents, communitarian and the teacher had been the main interlocutors of the research and its narratives had been distinguished as object of study and analysis. The theoretical bases used for analysis of the collected depositions were the studies of Apple, Arroyo, Vygotsky, Freire, Vasconcelos and Cagliari. The two first authors are included in the text becoming related it the depositions of the marginal citizens to the curriculum and its materialization, while the others had served of bases, for the analysis of the depositions referring to meanings of the curriculum. The study, the analyses focused the following thematic axles: The materialization of the curriculum in the multisseries riparian school; The curriculum and its meanings for the communitarian leaderships, parents of pupils and the teacher; The meaning of the pertaining curriculum school for the learners; The meaning of “learning to read” for riparian learners. This discussion is based on a qualitative boarding, and was developed through an exploratory research followed by the observation of the participants. Are used as methodologist technician procedures: half structuralized and narratives interviews, the documentary analysis of the curricular planning of the school, the used didactic book for reading of the learners in classroom; of photographic images and drawings of the students. As result, we identify that the multisseries riparian school needs more attention of the municipal government and the educators of better educative accompaniment and orientation in its practical; the practice of literation must assume as priority dimension in the initial series of basic education; An indifference in relation to the questions exists of: infrastructure, financial pedagogical didactic/and; the public politics of education of the city for the riparian school are precarious; what exist in thee multisseries school curriculum are a “listing of non contextualied contents” and the organization of the riparian education is basically “urbanistic”. It is indicated, therefore, the riparian education must be valued while space of construction of the knowledge, from the valuation of knowing cultural messengers to them, showing them for a reading of world and construction of new social and politicians citizens and syntonized with their territoriality and cultural identity.